Factors Affecting Palestinian Teachers' Ability to Reflect on Their Practice within Three Suggested Video-Enhanced Reflection Training Programs: Quasi-Experimental Research - Younis , Bilal Khaleel Mohammad (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to investigate the factors that affect teachers’ ability to reflect on their practice. Methods: In this study, a quasi-experiential design was used to compare three types of video-enhanced reflection programs: individual reflection, collaborative reflection in peer, and collaborative reflection in a group. A total of 106 science teachers were randomly assigned to these three groups. A four-point scale was used to assess three reflection assignments for each group for data collection. Results: The results showed that participating in the video-enhanced reflection group allowed teachers to write better reflections compared to participating in the video-enhanced individual or peer groups. This research revealed that teaching experience has a negative impact on teachers' ability to reflect on their practice. Furthermore, it found no significant difference between male and female teachers in their ability to reflect on their practice. Conclusions: The findings of this study support the notion that it is easier to convince younger teachers to use critical reflection in their practice, while older teachers may require additional training to embrace the values of critical reflection. Utilizing a heterogeneous group of teachers could be an effective method to help teachers learn and adopt critical reflection.